Manufacture of orthodontic implants by injection of titanium powders - Mallqui Espinoza, Marcos (2005)
This research aims to evaluate the manufacturing process of orthodontic implants by injection of titanium powders mixed with polymers. These parts are frequently manufactured by the machining process, a process of high cost and low productivity, due to the waste of the raw material and the various stages used in this process. The new process also generates a rough and porous surface that allows better osseointegration with the bone, this is due to the greater contact area generated by the process. It was observed that in the binder extraction stage (stage with the highest problem rate), several techniques were developed, using solvents or heat (chemical extraction or thermal extraction). The shape and size of the implants makes the extraction process difficult. Several tests will be carried out, and the results will be compared by means of extraction curves, determining the parameters of time, temperature, loss of mass and conservation of shape.